What determines if a ligand activates or passivates a superatom cluster?. Issue 5 (3rd February 2016) - Luo, Zhixun; Reber, Arthur C.; Jia, Meiye; Blades, William H.; Khanna, Shiv N.; Castleman, A. W.
Abstract : Quantum confinement in small metal clusters leads to a bunching of states into electronic shells reminiscent of shells in atoms, enabling the classification of clusters as superatoms. Abstract : Quantum confinement in small metal clusters leads to a bunching of states into electronic shells reminiscent of shells in atoms, enabling the classification of clusters as superatoms. The addition of ligands tunes the valence electron count of metal clusters and appears to serve as protecting groups preventing the etching of the metallic cores. Through a joint experimental and theoretical study of the reactivity of methanol with aluminum clusters ligated with iodine, we find that ligands enhance the stability of some clusters, however in some cases the electronegative ligand may perturb the charge density of the metallic core generating active sites that can lead to the etching of the cluster. The reactivity is driven by Lewis acid and Lewis base active sites that form through the selective positioning of the iodine and the structure of the aluminum core. This study enriches the general knowledge on clusters including offering insight into the stability of ligand protected clusters synthesized via wet chemistry.